Presence of Concomitant Systemic Cancer is Not Associated with Worse Functional Long-Term Outcome in Patients with Intracerebral Hemorrhage - Spuergel, Maximilian I.; Kuramatsu, Joji; Gerner, Stefan; Sembill, Jochen; Hartwich, Julius; Giede-Jeppe, Antje; Madzar, Dominik; Beuscher, Vanessa D.; Lücking, Hannes; Struffert, Tobias; Schwab, Stefan; Huttner, Hagen; et al. (Cerebrovascular Diseases, 2017)
Data on clinical characteristics and outcome of patients with intracerebral hemorrhage (ICH) and concomitant systemic cancer disease are very limited.Nine hundred and seventy three consecutive primary ICH patients were analyzed using our prospective institutional registry over a period of 9 years (2006-2014). We compared clinical and radiological parameters as well as outcome - scored using the modified Rankin Scale (mRS) and analyzed in a dichotomized fashion as favorable outcome (mRS = 0-3) and unfavorable outcome (mRS = 4-6) - of ICH patients with and without cancer. Relevant imbalances in baseline clinical and radiological characteristics were adjusted using propensity score (PS) matching.Prevalence of systemic cancer among patients with ICH was 8.5% (83/973). ICH patients with cancer were older (77 [70-82] vs. 72 [63-80] years; p = 0.002), had more often prior renal dysfunction (19/83 [22.9%] vs.107/890 [12.0%]; p = 0.005), and smaller hemorrhage volumes (10.1 [4.8-24.3] vs. 15.3 [5.4-42.9] mL; p = 0.017). After PS-matching there were no significant differences neither in mortality nor in functional outcome both at 3 months (mortality: 33/81 [40.7%] vs. 55/158 [34.8%]; p = 0.368; mRS = 0-3: 28/81 [34.6%] vs. 52/158 [32.9%]; p = 0.797) and 12 months (mortality: 39/78 [50.0%] vs. 70/150 [46.7%]; p = 0.633; mRS = 0-3: 25/78 [32.1%] vs. 53/150 [35.3%]; p = 0.620) among patients with and without concomitant systemic cancer. ICH volume tended to be highest in patients with hematooncologic malignancy and smallest in urothelial cancer.Patients with ICH and concomitant systemic cancer on average are older; however, they show smaller ICH volumes compared to patients without cancer. Yet, mortality and functional outcome is not different in ICH patients with and without cancer. Thus, the clinical history or the de novo diagnosis of concomitant malignancies in ICH patients should not lead to unjustified treatment restrictions.
EVALuna2:22553